ETHNOMEDICINAL PLANTS USED BY KORWA TRIBE OF KORBA DISTRICT, CHHATTISGARH – INDIA - Shukla, Sandeep (Current Botany)
The paper deals ethnomedicinal information of Korwa tribe of Korba district. The tribe still using several plants to cure different disease, 30 plants belonging to different families, with their botanical names, family, vernacular name, month of flowering part used and uses given here. Basically Chhattisgarh is “The land of tribe” and because of abundance of the tribe Korwa, this region was named Korba. The information was collected through survey. During the survey knowledgeable person, vaid, were interviewed and information recorded. The data indicate the uses of 30 ethnomedicinal plants used to cure different disease. The tribe residing in the forest continues to utilize their traditional system of cure which is still effective and these plants are having great socio-economic importance. There are so many other plants other than the mentioned and there is a need to record the maximum information.